2016
DOI: 10.12688/f1000research.8641.1
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic gradients in general and oral health of primary school children in Shiraz, Iran

Abstract: Background: Health status is largely determined by socio-economic status. The general health of individuals at higher social hierarchy is better than people in lower levels. Likewise, people with higher socio-economic status have better oral health than lower socio-economic groups. There has not been much work regarding the influence of socio-economic status on the health conditions of children in developing countries, particularly in Iran. The aim of this study was to compare the oral and general health condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In the present study, no significant difference was found between two genders in terms of the mean DMFT, which is consistent with some of the studies conducted in Iran on DMFT (17,19,20).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, no significant difference was found between two genders in terms of the mean DMFT, which is consistent with some of the studies conducted in Iran on DMFT (17,19,20).…”
Section: Discussionsupporting
confidence: 93%
“…However, in our study, the relationship between socioeconomic status of the family and the quality of life and the DMFT index was not significant. In Golkari et al study in Shiraz city, a direct relationship was found between the socioeconomic level of family and OHRQOL (17). Also, in the study conducted by Nanayakkara et al there was a direct relationship between low family income and low education of parents with increased dental caries (16).…”
Section: Discussionmentioning
confidence: 96%
“…In addition to the social gradient, health behaviours are also involved in the development of diseases, suggesting the existence of a social/behavioural gradient. 1 , 2 …”
Section: Introductionmentioning
confidence: 99%
“…A disproportionate burden of defects is shouldered by marginalized, low-income populations (Psoter et al 2005; Golkari et al 2016). There is evidence that systemic factors associated with developmental enamel defects include disease, macronutrient and micronutrient deficiencies, chronic conditions, excessive fluoride exposure, and/or prolonged use of certain medications.…”
mentioning
confidence: 99%